Cover Image, Volume 38, Issue 9. (6th August 2018) - Eastwood, Mary Patrice; Deprest, Jan; Russo, Francesca Maria; Wang, Hongmei; Mulhall, Drew; Iwasiow, Barbara; Mahood, Thomas H.; Keijzer, Richard
Abstract : GD30 DH lung showing higher expression of miR‐200b particularly in alveoli. From Eastwood et al., in this issue.https://doi.org/10.1002/pd.5318 .